(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
The study was conducted to determine the level of accumulation of arsenic concentration in lungs, intestine, gizzard and skin of broilers. Forty eight apparently healthy day-old “Star-bro” broiler chicks (already vaccinated with Marek’s disease vaccine in the hatchery) were reared up to 34 days. All chicks were reared in the same brooder up to 7 days of age and then all broiler chicks (48) were divided into 4 different groups; Group-A, Group-B, Group-C and Group Control each consisting of 12 chicks. Birds of Group-A, B, and C were given 1, 0.5, and 0.25 ppm arsenic, respectively mixing with drinking water (distilled water). No arsenic treatment was given in the Control Group. Two birds from each group were selected randomly for slaughter at the day of 14, 21, 28, 30, 32 and 34, respectively. Body weight was noted down and external examination was performed before post mortem examinations. After collection, the samples were prepared by a series of steps such as, washing, drying and digestion; finally arsenic was detected by atomic absorption spectophotometric method. The mean highest arsenic concentration in lungs, intestine, gizzard and skin were 1.027±0.1265 ppm in Group-B, 0.422±0.0228 ppm in group-A, 0.2885±0.032 ppm in group-B, 0.3198±0.057 ppm in group-A (in all case n=6), respectively. In this study it was found that the level of arsenic in lungs, intestine, gizzard and skin is greater than that of the maximum permissible level in drinking water (0.05ppm, WHO). From the findings of the present study gives an indication of severe human health hazards caused by arsenic through animals as well as agro based human food which is still unnoticed. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (2), 190-198